Circular economy in the olive oil value chain: assessment of by-product generation in the main olive-growing area of Argentina, San Juan - Renzi, Laura Andrea; Alday Poblete, Silvina Esther; Monetta, Pablo Miguel (INTA y Sbera, 2025)
Poster